Cover - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Analysis of the impact of soil excavation stages on slope stability case study of road and bridge construction projects in bts. Singaraja-Mengwitani at point 7E, Bali Guilden Laelatu Yudha, Ria Asih Aryani Soemitro, Trihanyndio Rendy Satrya &Noor Fachrie Planning of Alternative Embankment Reinforcement on the Roadway. Case Study: Landslide on the Bypass Road of Lombok International Airport - Mandalika Section Km 10+415 to 10+519 Panji Ageng Ichtiar, Mohamad Khoiri, Dwa Desa Warnana & Herlambang Zulfikar Analysis of the Use of a Combination of Soil Embankment and Lightweight Material (Foam Mortar) as an Alternative to Slab on Pile Construction Case Study: Rengat-Pekanbaru Toll Road Construction Project Section Lingkar Pekanbaru-Junction Pekanbaru Sta 193+ 025 - 193+400 I Wahyu Maya Dewatama, Noor Endah Mochtar, Indrasurya B. Mochtar & Mahar Muliawan Comparison Between Soil Improvement Design Method Of Replacement And PVD Installation For Soft Soil Embankment, Case Study: Probolinggo – Banyuwangi Toll Road Project Section 3 Sta 23+075 – 23+670 Esti Kusuma Wardani & Reza Kazhimi Slope Design for Cost Optimization of Slope Cutting and Reinforcement (Case Study: Trans-Sumatra Toll Road Rengat Pekanbaru Section Lingkar Pekanbaru Junction Pekanbaru Sta. 205+150 - 205+725) R Fiansyah Dwi Prasetiyo, Noor Endah Mochtar, Indra Surya B Mochtar & Mahar Muliawan